DESENTRALISASI PENDIDIKAN PELUANG DAN TANTANGAN - Harahap, Lazuardi (FORUM PAEDAGOGIK, 2013)
AbstractDecentralization in education has an opportunity and chalenging, the government and the doer of education must be clever in filling it with the good site and rejecting it with good moral and attitude.Key Words: education, decentralization.